Improving Students’ Vocabulary Mastery through Fun Thinkers Media: : Case Study for the First Year- Autistic Students of SMP Negeri 3 Hutabayuraja - Melisa Carolina Sianturi; Sahlan Tampubolon; Lastri W. Manurung (UIBU, 2023)
This research examines the vocabulary knowledge abilities of autistic students in English subjects at SMP Negeri 3 Hutabayuraja. According to Zuchdi (1995: 3-7) vocabulary mastery is a person's ability to recognize, understand and use words well and correctly by listening, speaking, reading and writing.The research's formulation of the issue is